Stability analysis for grain yield and its components under different moisture regimes in bread wheat (Triticum aestivum) - KUMAR, VISHNU; TYAGI, B S; VERMA, AJAY; SHARMA, INDU (The Indian Journal of Agricultural Sciences, 2014)
The present study was undertaken to identify stable genotypes for grain yield and its components with resilient performance under water deficit and irrigated conditions in bread wheat (Triticum aestivum L.). The combined analysis of variance depicted significant g × e interaction mean squares for all the characters, except spike length and peduncle length. The highest pooled mean for grain yield/plant ranged from 4.98 to 7.05 g and the highest mean was exhibited by Raj 4037 (7.05 g) followed by PBW 373 (6.96 g), GW 273 and WR 544 (both 6.89 g) etc, respectively. For 1000 grain weight the genotypes, viz. DPW 621-50 (µ=36.67 g, b=1.01** and S2di=-0.54) followed by UP 2425 (µ=36.67 g, b=0.89** and S2di=-0.56) and Raj 4037(µ=36.50 g, b=0.95 and S2di=-0.58) showed stable performance across the environments. The genotypes namely, viz. WR 544, GW 273, DBW 39, HD 2987, Raj 3777, UP 2425, Raj 3765, PBW 343 and UP 2338 revealed consistent performance for high biomass and grain yield in water stress and as well as in irrigated conditions.